Improvement of yield for a tropical black bolete, Phlebopus portentosus, cultivation in northern Thailand - Kumla,J. (Springer Japan, 2015)
© 2014 The Mycological Society of Japan. Published by Elsevier B.V. All rights reserved. Phlebopus portentosus is an edible bolete mushroom with the ability to produce fruiting bodies in the absence of a host plant. In this study, the improved yield of P. portentosus cultivation was evaluated. As a supplemental solution, fungal host solution was found to be better comparing with two other solutions. Cultivation experiment indicated that both the highest number of primordial formation and yield of fruiting bodies were obtained on 1:1 (v/v) of mixed sorghum grains supplemented with fungal host solution and sawdust. The identification of cultivated fruiting bodies was confirmed by both morphological and molecular methods.